Extraction rate of valuable compounds from peanut skin waste by ethanol-assisted supercritical carbon dioxide: Modelling and optimization - Nicky Rahmana Putra; Dwila Nur Rizkiyah; Ahmad Hazim Abdul Aziz; Zuhaili Idham; Lailatul Qomariyah; Mohd Azizi Che Yunus (Penerbit UTM Press, 2022)
Response Surface Methodology (RSM) was employed to optimize the extraction rate of phenolic and flavonoid contents from peanut skin by supercritical carbon dioxide (ScCO2) assisted by ethanol as entrainer. The studied extraction parameters were pressure (10 to 30 MPa), temperature (40 to 70 oC), and the ratio of ethanol (2.5 to 7.5%). Brunner’s and Esquivel’s models were applied to evaluate the extraction rate. The best-operating conditions, in the tested range, were 30 MPa, 40 °C, and 4.64% of ethanol ratio, with a maximum extraction rate of 0.22 mg/g.sec and 0.19 mg/g.sec of the phenolic and flavonoid content, respectively. The findings concluded that higher-pressure condition has a significant impact on the extraction rate of phenolic and flavonoid